Pesan Emosi Orangtua Terhadap Regulasi Emosi Anak Usia Prasekolah Selama Pendidikan Jarak Jauh - Reno Intan; Naila Attamimi; Neneng Alawiyah (stit-islamic-village, 2023)
Emotion communication between parents and pre-schooler have been proven to have a significant part in children’s emotion regulation development. Particularly in this pandemic time, where early childhood has to spend more time at home due to stay-at-home instruction. Research purpose is to determine the effect of communication emotion to children emotion regulation. Population is parents with preschool children in Kabupaten Tangerang. Simple random sampling is used to decide to sampling; with total participant 51 parents (father or mother). Emotion communication between parent-child will be measured using rating scale Parents-Child Conversations about Emotion/QPCCE and the child emotion regulation will be measured using the Emotion Regulation Skills Questionnaire. Results show that there are no significance effect in communicating emotion to preschool emotion regulation. For future research, it is suggested to simplify the questionnaire.